Enhanced neutrophil phagocytic capacity in rheumatoid arthritis related to the autoantibodies rheumatoid factor and anti-cyclic citrullinated peptides - de Siqueira, Marcelo Bogliolo Piancastelli (BMC Musculoskelet Disord, 2015)
BACKGROUND: There is no consensus on the mechanisms by which anti-cyclic citrullinated peptide antibodies (anti-CCP) and rheumatoid factor (RF) influence the pathogenesis of rheumatoid arthritis (RA). The current study verified if the presence of RF or anti-CCP is associated with phagocytic capacity and reactive oxygen species (ROS) production by phagocytes in RA patients to better clarify the role played by these antibodies in pathogenesis of the disease. METHODS: A cohort of 30 RA patients followed from early stages of the disease were characterized by positivity for RF or anti-CCP, disease activity score (DAS-28), health assessment questionnaire (HAQ), use of synthetic or biologic therapy, lifestyle, comorbidities and radiographic erosions. Phagocytic capacity against Saccharomyces cerevisiae and superoxide anion production were assessed in RA patients and compared with 20 healthy controls. Phagocytic capacity and superoxide anion production were also compared between RF- and anti-CCP-positive and -negative RA patients. RESULTS: Anti-CCP- and RF-positive RA patients had higher neutrophil phagocytic capacity than anti-CCP- (p = 0.005) and RF (p = 0.005)-negative individuals through pattern-recognition receptors. As assessed via pattern recognition or opsonin receptors, neutrophils and monocytes from RA patients presented overall higher phagocytic capacity than neutrophils and monocytes from healthy controls (p < 0.05). Furthermore, RA patients also showed a higher capacity for producing cytotoxic oxygen radicals (p = 0.0026). Phagocytosis and superoxide anion production did not correlate with any of the clinical variables analyzed in this study. CONCLUSIONS: This study showed increased phagocytosis by neutrophils in RA patients who were positive for anti-CCP and RF autoantibodies. Furthermore, there was an overall hyperactivation of the phagocytes in RA patients. Our data suggest that anti-CCP and RF may indirectly enhance the inflammation cascade involving neutrophils and may indirectly sustain tissue damage in RA. Targeting the production of these autoantibodies may be a promising strategy in the management of RA.